Impact and Effectiveness of 10 and 13-Valent Pneumococcal Conjugate Vaccines on Hospitalization and Mortality in Children Aged Less than 5 Years in Latin American Countries: A Systematic Review. - Lucia Helena de Oliveira; Luiz Antonio B Camacho; Evandro S F Coutinho; Martha S Martinez-Silveira; Ana Flavia Carvalho; Cuauhtemoc Ruiz-Matus; Cristiana M Toscano (PLoS ONE)
Background Several Latin American and Caribbean (LAC) countries have introduced pneumococcal conjugate vaccine (PCV-10 or PCV-13) in their routine national immunization programs. Objectives We aimed to summarize the evidence of PCV impact and effectiveness in children under 5 years old in the LAC Region. Methods We conducted a systematic review of the literature on impact or effectiveness of PCVs on deaths or hospitalizations due to invasive pneumococcal disease (IPD), pneumonia, meningitis and sepsis. We searched Medline, WoS, Lilacs, Scopus, Central and gray literature published in any language from 2009 to January 2016. We included studies addressing the outcomes of interest in children in the target age group, and with the following designs: randomized trials, cohort or case-control, interrupted time series with at least three data points before and after the intervention, and before-after studies. Screening of citations, data extraction, and risk of bias assessment were conducted in duplicate by independent reviewers, according to the study protocol registered on PROSPERO. Descriptive analysis of the effectiveness measurements and sensitivity analysis were conducted. Effectiveness is reported as 1-OR or 1-RR for case control or cohort/clinical trials, and as percent change of disease incidence rates for before-after studies. Results We identified 1,085 citations, 892 from databases and 193 from other sources. Of these, 22 were further analyzed. Studies were from Brazil, Chile, Uruguay, Argentina, Peru and Nicaragua. Effectiveness ranged from 8.8-37.8% for hospitalizations due to X-ray confirmed pneumonia, 7.4-20.6% for clinical pneumonia, and 13.3-87.7% for meningitis hospitalizations, and 56-83.3% for IPD hospitalization, varying by age, outcome definition, type of vaccine and study design. Conclusions Available evidence to date indicates significant impact of both PCV-10 and PCV-13 in the outcomes studied, with no evidence of the superiority of one vaccine over the other on pneumonia, IPD or meningitis hospitalization reduction in children under 5 years old.